Reptile responses to anthropogenic habitat modification: A global meta‐analysis. Issue 7 (20th March 2020) - Doherty, Tim S.; Balouch, Sara; Bell, Kristian; Burns, Thomas J.; Feldman, Anat; Fist, Charles; Garvey, Timothy F.; Jessop, Tim S.; Meiri, Shai; Driscoll, Don A.
Abstract: Aim: The aim was to determine how reptile populations respond to anthropogenic habitat modification and determine whether species traits and environmental factors influence such responses. Location: Global. Time period: 1981–2018. Major taxa studied: Squamata. Methods: We compiled a database of 56 studies reporting how habitat modification affects reptile abundance and calculated standardized mean differences in abundance (Hedges' g ). We used Bayesian meta‐analytical models to test whether responses to habitat modification depended on body size, clutch size, reproductive mode, habitat specialization, range size, disturbance type, vegetation type, temperature and precipitation. Results: Based on 815 effect sizes from 376 species, we found an overall negative effect of habitat modification on reptile abundance (mean Hedges' g = −0.43, 95% credible intervals = −0.61 to −0.26). Reptile abundance was, on average, one‐third lower in modified compared with unmodified habitats. Small range sizes and small clutch sizes were associated with more negative responses to habitat modification, although the responses were weak and the credible intervals overlapped zero. We detected no effects of body size, habitat specialization, reproductive mode (egg‐laying or live‐bearing), temperature or precipitation. Some families exhibited more negative responses than others, although overall there was no phylogenetic signal in the data. Mining had the most negative impacts on reptile abundance, followed by agriculture, grazing, plantations and patch size reduction, whereas the mean effect of logging was neutral. Main conclusions: Habitat modification is a key cause of reptile population declines, although there is variability in responses both within and between species, families and vegetation types. The effect of disturbance type appeared to be related to the intensity of habitat modification. Ongoing development of environmentally sustainable practices that ameliorate anthropogenic impacts is urgently needed to prevent declines in reptile populations.